Exosome Component 4 Promotes Epithelial Ovarian Cancer Cell Proliferation, Migration, and Invasion via the Wnt Pathway - Xiong, Chang; Sun, Zhongfeng; Yu, Jinjin; Lin, Yaying (Frontiers in Oncology, 2021)
Background: Of gynecologic malignancies, ovarian cancer is the leading cause of death, mainly due to the lack of sensitive tumor markers, which means it almost always presents at an advanced stage. Exosome Component 4 (EXOSC4) is involved in RNA degradation, but its role in epithelial ovarian cancer (EOC) is unclear. Methods: The expression levels of EXOSC4 in EOC and normal ovarian tissue specimens were determined by immunohistochemical staining. The overall survival (OS) and progression-free survival (PFS) of patients with EOC were evaluated after patients were classified into high and low EXOSC4 expression groups, and the Cox regression model was established to identify independent predictors of patient prognosis. The effects of EXOSC4 on proliferation, colony formation, migration, and invasion were examined in the SKOV-3 and HO8910 cell lines by lentivirus-mediated shRNA knockdown. Flow cytometry was used to detect cell cycle changes. The mRNA levels of cyclin D1, CDK4, and c-myc were detected by RT-PCR. The protein expression levels of β-catenin, cyclin D1, CDK4, c-myc, vimentin, N-cadherin, and E-cadherin were assessed by western blot. Wnt/β-catenin activation was measured by TCF/LEF reporter assay. Results: EXOSC4 was significantly elevated in EOC tissues and cell lines. High EXOSC4 expression was correlated with the International Federation of Gynecology and Obstetrics (FIGO) stage and pathological grade, and identified as an independent predictor of shorter OS and PFS. EXOSC4 knockdown suppressed proliferation, migration, and invasion in EOC cell lines. Cells were arrested at G0/G1 phase after EXOSC4 knockdown. The mRNA levels of cyclin D1, CDK4, and c-myc were decreased. β-catenin, cyclin D1, CDK4, c-myc, vimentin, and N-cadherin protein expression levels were reduced, while those of E-cadherin was increased. Wnt/β-catenin activity was suppressed after the EXOSC4 knockdown. Conclusions: EXOSC4 is involved in EOC. Knockdown of EXOSC4 can inhibit the proliferation, migration, and invasion ability of EOC by suppressing the Wnt pathway. EXOSC4 is expected to be a novel biomarker and molecular target in EOC.